The importance of interfacial design for the sensitivity of a label-free electrochemical immuno-biosensor for small organic molecules - Khor, S.M.; Liu, G.; Fairman, C.; Iyengar, S.G.; Gooding, J.J. (Elsevier, 2011)
An immuno-biosensing interface comprising a mixed layer of an oligo(ethylene glycol) (OEG) component, and an oligo(phenylethynylene) molecular wire (MW) is described. The OEG controls the interaction of proteins and electroactive interferences with the surface and the MW allows electrochemical communication to the underlying glassy carbon electrode. The layers are formed from in situ generated-aryl diazonium cations. To the distal end of the MW, a redox probe 1,1-di(aminomethyl)ferrocene is attached followed by the surface bound epitope (the structural feature the antibody selectively recognizes) to which an antibody would bind. Association or disassociation of the antibody with the sensing interface causes a modulation of the ferrocene electrochemistry. X-ray photoelectron spectroscopy, cyclic voltammetry, and square wave voltammetry have been used to characterize the step-wise fabrication of the sensing interface. The influence of the molar ratio of the MW and OEG deposited onto the sensor interface was explored relative to the final sensor sensitivity. Five combinations of MW/OEG 1:0, 1:20, 1:50, 1:75 and 1:100 were tested on sensor sensitivity detection for a model analyte (biotin) free in solution, via a displacement assay. The ratio of 1:50 was found to give the highest sensitivity. At this ratio, good reproducibility (RSD 6.8) and repeatability (RSD 9.6) was achieved. This immuno-biosensor provides an intervention free immuno-biosensing platform for agriculture and biomedical samples.